Longer apnea duration at low altitude in Tibetan and Han highlanders compared with Han lowlanders: A retrospective study. (23rd October 2019) - Tan, Lu; Li, Taomei; Lei, Fei; Li, Xiao; Zhou, Junying; Zhang, Ye; Ren, Rong; Yang, Linghui; Tang, Xiangdong
Abstract: Prolonged duration of obstructive apnea (OA) has been observed in highlanders after descending to low altitude. It is proposed that due to adaptation to a hypoxic high‐altitude environment, Tibetan highlanders (TH) and Han highlanders (HH) would manifest different OA durations at low altitude as compared to Han lowlanders (HL). Data collection on consecutive obstructive sleep apnea patients (167 TH, 210 HH and 233 HL) was performed over a period of 8 years in Chengdu (altitude 500 m). The analyses were performed with non‐matched groups and with body mass index and apnea–hypopnea index‐matched groups. Significance rankings for mean duration of OA (s) in non‐matched groups and matched groups were TH (27.7; 28.6) = HH (25.7; 26.0) > HL (21.7; 21.3), respectively. For the longest OA duration, the significance rankings across three groups with regard to the percentage of patients having a duration longer than 2 min (%) and mean values (s) were TH (26.9; 82) > HH (10.0; 67) > HL (1.3; 50). In terms of nadir and mean oxygen saturation, significant differences were found between TH and HH or HL. In addition, longest and mean OA duration were positively correlated with blood pressure and heart rate, whereas nadir and mean oxygen saturation were negatively correlated with these measures in both non‐matched and matched groups, and the correlation was more robust in TH. These findings raise important clinical questions regarding whether such significant prolongation of OA duration and a more severe hypoxic burden among highlanders, especially in TH, may lead to adverse clinical consequences when at low altitude.